A LabVIEW based data acquisition system for vibration monitoring and analysis - Abdul Muthalif, Asan Gani; Salami, Momoh Jimoh Eyiomika (2002)
LabVIEW (Laboratory Virtual Instrument Engineering Workbench) is gaining its popularity as a graphical programming language especially for data acquisition and measurement. This is,due to the vast array of data acquisition cards and measurement systems, which can be supported by the LabVIEW as well as the relatively easy by which advanced software can be programmed. One area of application of LabVIEW is in the monitoring and analysis of vibration signals. The analysis and monitoring of the signal are of the concem for fault detection and implementing predictive maintenance. This paper describes a LabVIEW based data acquisition and analysis developed specifically for Vibration monitoring and used with Vibration Faults Simulation Systems (VFSS). On-line displays of time and frequency domain of the vibration signal provide a user-friendly data acquisition interface